Особенности выявления дефектов тонких электропроводящих пленок - Светличный, Виталий Анатольевич; Хорошайло, Юрий Евгеньевич; Мулявка, Олег Владиславович; Сова, Анна Васильевна (НТУ "ХПИ", 2017)
В результате изучения свойств и структуры тонких пленок, показано что свойства и структура тонких пленок значительно отличается от тех же параметров объемного материала. Физические процессы происходящие во время образования пленок обуславливают индивидуальную специфику свойств и структуры. Поэтому, одним из основных показателей качества металлических тонких пленок является отсутствие дефектов. В работе рассмотрены вопросы теории появления дефектов тонких электропроводящих пленок. Выполнен анализ влияния главных электрических параметров пленок на наличие дефектов структуры пленок. Показаны иные возможные виды дефектов пленок и определены способы их выявления.

As a result of studying the properties and structure of thin films, it is shown that the properties and structure of films differ significantly from the properties and structure of bulk material of the same composition. The physical processes that occur during the formation of films cause the individual specificity of the properties and structure. Therefore, one of the main indicators of the quality of metallic thin films is the absence of defects. The paper deals with the theory of the appearance of defects in thin electrically conductive films. The analysis of the effect of the main electrical parameters of the films on the presence of defects in the structure of the films is performed. Other possible types of defects of films are shown and methods for their detection.
Features of the detection of defects in thin electrically conductive films
Keywords: форма пленки; толщина пленки; пористость структур; поверхностная плотность островков; дефекты; porosity of structures; surface density of islands